2019
DOI: 10.3390/coatings9020104
|View full text |Cite
|
Sign up to set email alerts
|

Biocleaning to Remove Graffiti: A Real Possibility? Advances towards a Complete Protocol of Action

Abstract: The first academic studies on the use of microorganisms in cleaning procedures appeared in the late 1980s/early 1990s. In the past thirty years, most of such studies have addressed the removal of nitrate and sulphate salts and organic matter from surfaces by using non-pathogenic anaerobic microorganisms, mainly sulphate-reducing bacteria. The successful use of microbes in the removal of graffiti paint remains, however, a work in progress. Biocleaning surfaces to remove graffiti is not a simple task, because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Biocleaning approach has recently been evaluated also for the removal of graffiti paint, a very common cause of disfigurement of monuments, buildings and other urban structures. Sanmartin et al investigate an efficient biocleaning protocol for in situ application, reducing time of treatment and using a specific culture medium for the adaptation of bacteria to target substrate [82][83][84].…”
Section: Biocleaningmentioning
confidence: 99%
“…Biocleaning approach has recently been evaluated also for the removal of graffiti paint, a very common cause of disfigurement of monuments, buildings and other urban structures. Sanmartin et al investigate an efficient biocleaning protocol for in situ application, reducing time of treatment and using a specific culture medium for the adaptation of bacteria to target substrate [82][83][84].…”
Section: Biocleaningmentioning
confidence: 99%
“…Successful application of bacteria for biotreatment of different materials ( Table 2 ), was shown i.e., for Thiobacillus denitrificans for FeS and mineral sulfur transformation for historical wood treatment [ 131 ] or Pseudomonas stutzeri , Aerobacter aerogenes , Comamonas sp. for graffiti cleaning [ 132 ]. Animal glues were often used in paper manufacturing and reparation of ancient paper artworks, but aged glue can create distortions, tensions, cockling and discoloration of paper materials.…”
Section: Biotechnological Use Of Microorganisms In Cultural Heritamentioning
confidence: 99%
“…Microorganisms become virtuous when used for the removal of harmful compounds from CH [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. In the last two decades, many applied studies have shown that biocleaning of altered CH surfaces has some advantages over the traditional cleaning methods; indeed, chemical treatments are not always sufficiently selective consequently damaging stone surfaces [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%